Faunistic Study on Butterflies in the Lowland Forests of Central Surigao del Sur, Philippines - GRACIA JR., ARTURO GASCON; ALBIOS, LAURENCE PINGOL; ALVERO, ROMART LLOYD BALBUENA (Borneo Journal of Resource Science and Technology, 2021)
The province of Surigao del Sur is among the areas in the Philippines with limited wildlife studies, especially on lepidopteran fauna. Thus, this study was conducted to evaluate the butterfly congregation and diversity in Gamut and Mat-e, areas which are underexplored for lepidopteran surveys. It also aimed to assess the conservation and ecological status of the species. Sweep netting for a total of 196 person-hours was carried out to document the species. The results revealed a total of 29 species belonging to four families. Among the families, Nymphalidae was the most represented, comprising 48% of the total richness. The species Gandaca harina mindanaensis and Junonia hedonia ida were the most dominant in both sites representing 12% (each) of the total population. Species richness and diversity (H’) were relatively higher in Mat-e (n=22; H’=1.22) than in Gamut (n=15; H’=1.00). The total endemicity was 31%, but higher endemism was observed in Mat-e (36%) compared with Gamut (20%). The noteworthy findings are the listing of the nationally and globally assessed as rare species (Acrophtalmia leto ochine and Jamides celeno), but were locally assessed as common in Mat-e. One recorded butterfly (Atrophaneura semperi aphtonia) was assessed to be a threatened species. Based on the results, the two habitats showed a poor representation of butterfly assemblage, however, these results are highly affected by the limitations of the observation. Thus, it is recommended that an intensive study on butterflies in the area should be considered.